Plant bugs of the tribe Bothriomirini (Hemiptera: Heteroptera: Miridae: Cylapinae) from the Oriental Region: descriptions of eight new species and keys to Oriental genera and species of Bothriomiris Kirkaldy, Dashymenia Poppius, and Dashymeniella Poppius - Wolski, Andrzej; Gorczyca, Jacek (Zootaxa, 2012)
Eight new species of the tribe Bothriomirini are described from the Oriental Region, namely Dashymenia cognata sp. nov., Dashymenia colubrina sp. nov., Dashymenia conspersa sp. nov., Dashymenia tenmalai sp. nov., Dashymenia webbi sp. nov., Dashymeniella spatulatiformis sp. nov., Dashymeniella ulu sp. nov., and Dashymeniella viklundi sp. nov. Five species are redescribed: Bothriomiris dissimulans (Walker), B. lugubris Poppius, B. testaceus Distant, Dashymenia croesus (Distant), and Dashymenia remus (Distant). Illustrations of the male genitalia, a color dorsal habitus photograph of the adult of most species, scanning electron micrographs of selected structures of Bothriomiris dissimulans, Dashymenia tenmalai, Dashymeniella spatulatiformis, and Dashymeniella ulu are given. An identification key to the Oriental genera and keys to species of the genera Bothriomiris, Dashymenia, and Dashymeniella are provided.